Magma storage conditions below Eyjafjöll, based on clinopyroxene macrocrysts and gabbro xenoliths from Seljalandsheiði and Brattaskjól, Iceland - Bryndís Ýr Gísladóttir 1992- (2018)
Large clinopyroxene macro- and megacrysts along with gabbroic-xenoliths were discovered in the Upper Pleistocene “ankaramite” outcrops of Seljalandsheiði and Brattaskjól from Eyjafjallajökull, in the Eastern Volcanic Zone of Iceland. The pyroxenes are mostly of augite composition, though a few can be classified as diopside. The pyroxenes display a considerable range in magnesium-value (Mg#: 57.9-83.3) and also in their minor oxides such as TiO2 (0.00-2.46 wt%), Al2O3 (0.03-6.28) and Cr2O3 (0.0-0.99). Most pyroxenes are strongly zoned where normal-, reverse-, oscillatory-, sector- and patchy zoning was observed. Magma mixing can possibly explain the presence of inverse zoning patterns. The gabbroic-xenoliths are of two types, olivine-bearing gabbro and olivine-free gabbro. Crystallization depths were obtained using a newly published clinopyroxene-melt thermobarometer from Neave and Putirka (2017). Clinopyroxene macro- and megacrysts crystallized at 1035-1150°C and 0.0-5.8 kbars pressure, corresponding to 0.0-16.2 km depth. The crystallization conditions of these macrocrysts are thus very similar to those observed for crystals of the 2010 flank eruption of Fimmvörðuháls and the summit eruption of Eyjafjallajökull. This suggest that crystallization depths beneath Eyjafjallajökull has not change significantly since the Upper Pleistocene. In contrast, olivine-bearing gabbroic-xenoliths crystallized at a more restricted depth range of 3.8-5.6 kbars and 1140-1160°C (10.6-15.6 km depth) whereas olivine-free xenoliths are likely to be widespread in the middle to upper crust beneath Eyjafjallajökull, forming between 1070-1180°C and 0.1-5.3 kbars (0.0-14.8 km depth). Finna má stóra pýroxen-kristalla og gabbró-hnyðlinga í ísaldarhrauneiningum á Seljalandsheiði og nærri Brattaskjóli við Eyjafjallajökul. Pýroxenarnir eru að mestu ágít, en nokkra má skilgreina sem díopsíð. Magnesíum-gildi (Mg#) pýroxenanna er breytilegt frá 57,9-83,3 sem og styrkur annarra oxíða, eins og TiO2 (0,00-2,46 wt%), Al2O (0,003-6,28 wt%) og Cr2O3 ...